1980
DOI: 10.1002/bjs.1800670217
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal biopsy of the prostate and bacteraemia

Abstract: Bacteraemia and urinary tract infection are well-recognized complications of urological procedures. This paper compares, for the first time, the incidence of bacteraemia after cystoscopy and transrectal biopsy of the prostate with that following cystoscopy alone. The incidence of bacteraemia in those undergoing biopsy was 73 per cent; following cystoscopy alone the incidence was 13 per cent. In view of this high incidence we recommend prophylactic antibiotic cover of transrectal prostatic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Others demonstrated that approximately 70% of patients [4,8,9] experienced transitory bacteremia and between 21% and 53% [4,10] showed significant bacteriuria during or immediately after the procedure. These findings led several authors to investigate different preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Others demonstrated that approximately 70% of patients [4,8,9] experienced transitory bacteremia and between 21% and 53% [4,10] showed significant bacteriuria during or immediately after the procedure. These findings led several authors to investigate different preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Although many studies have reported the incidence of complications, they were not specifically designed to evaluate the true complication rate and its implications. [8][9][10][11][12] It is essential to have a clear understanding of the true morbidity of this procedure, and this would enable appropriate patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al berichteten von signifikanten Bakteriämien nach transrektaler Prostatabiopsie in 73±100 % [19,20]. Die Häufigkeit entzündlicher Komplikationen kann durch eine prophylaktische Antibiotikagabe verringert werden [6,7,15].…”
Section: Materials Und Methodeunclassified